Assessing the therapeutic potential of Ganoderma lucidum spore oil in alleviating periodontal tissue damage in murine periodontitis model - Ji-Hyun Kim; Weon-Young Choi; Seung-Jun Jeong; Ka Hyon Park; Gyuseok Lee; Mangeun Kim; Soo-Chang Joo; Seongjun Kim; Beom-Jin Cho; Young-Ok Son; Je-Hwang Ryu (Applied Biological Chemistry, 2024)
Abstract Periodontal disease presents a significant challenge in oral health due to its chronic inflammatory nature and subsequent degradation of tooth-supporting structures. Natural compounds have attracted attention for their potential therapeutic effects in alleviating symptoms of periodontitis (PD). In this study, we investigated the impact of Ganoderma lucidum spore oil (GLSO), a lipid component extracted from broken-walled GLS using the supercritical CO2 extraction method, on PD pathogenesis in vitro and in vivo. Treatment of human gingival fibroblasts with GLSO resulted in a significant reduction in the expression of inflammatory factors, including matrix metalloproteinase (MMP)-1 and interleukin (IL)-8, upregulated by lipopolysaccharide or IL-1β. Molecular mechanism studies revealed that the observed decrease in inflammatory factor expression may be attributed to the inhibition of phosphorylated c-Jun N-terminal kinase activity by GLSO. Furthermore, intraperitoneal injection of GLSO in a ligature-induced PD mouse model led to a notable reduction in periodontal inflammation and alveolar bone loss, accompanied by decreased levels of MMP-1 and IL-8. These in vivo results support the potential therapeutic efficacy of GLSO in alleviating PD symptoms. Overall, our study provides novel insights into the beneficial effects of GLSO in PD management. Further research is warranted to elucidate the underlying molecular mechanisms and explore the clinical applicability of GLSO as a promising therapeutic agent for PD treatment.